MSME Business Management and Development with IFE-EFE Matrix - Rousilita Suhendah; Angelina Angelina; Rico Ricardo; Nikita Stevansyah (Journal of Innovation and Community Engagement, 2022)
The empowerment of MSMEs is an important thing. MSMEs empowerment aims to enable MSMEs to continue, develop and create employment opportunities for the surrounding population. Empowering MSMEs includes improving management and implementing appropriate strategies so that MSMEs can continue to survive in the future. MSMEs Go Nads, which engaged in fashion making of clothes made from traditional Indonesian fabrics, face the same problems as other MSMEs. This problem is an obstacle in developing Go Nads MSMEs. Internal and external factors from MSMEs are a constraint for MSMEs' growth. Internal factors include limited competency in human resources, capital, a simple business network, and limited ability to penetrate the market. External factors include limited facilities and infrastructure, free competition, and a business climate that does not support MSME activities. Therefore, the Untar team carried out community service activities by providing training on business management and development by making the IFE-EFE matrix. Matrix Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) is a tool to formulate a strategy consisting of internal and external factors. Internal factors are strengths, weaknesses, and external factors in the form of opportunities and threats that can occur in a business venture. The internal and external data is collected to analyze, identify and evaluate the relationship between the two so that it can implement business strategies, especially for MSMEs. The IFE and EFE matrices determine the position of MSMEs and the preparation of business strategies. The results of this PKM activity are that Go Nads MSMEs are in Quadrant I in the IE matrix. The position of the 1st Quadrant in the IE (Internal External) matrix shows the Go Nads SMEs position is in the growth and development stage. The right strategy is to penetrate the market and develop the market.